Program Pengabdian masyarakat KEGIATAN PENANAMAN 1000 POHON ALPUKAT DI LUT ATAS KECAMATAN BUKIT KABUPATEN B ENER MERIAH UNTUK MEWUJUDKAN HUTAN LESTARI MASYARAKAT SEJAHTERA - Harinawati; Ratri Candrasari (UII, 2023)
The Community Service Program is one of Tridharma programs in Higher Education, in this case the academic community carries out activities of planting 1000 Avocado Trees in order to create the Sustainable Forest of Prosperous Communities. Lut Atas is a village forest area located in Waq Pondok Sayur sub-district, Bukit District, Bener Meriah Regency, with Village Forest Management reaching 813 Ha for 35 years service. The community can take non-timber forest products. One of the efforts made is by planting avocado trees in the Village Forest Area with the hope that the community can pick them after the harvest arrives, without destroying the forest. As a moral responsibility, the lecturers of the Communication Studies Program supported by the Menwa Student Association, Scouts, Unpal (Nature-loving students), Himako (Communication Science Student Association), Himaga (Gayo Student Association) carrid out the service program of planting 1000 Avocado Trees in the area of Lut Atas and Waq Pondok Sayur. This program received a positive response from local Muspika elements. The agroforestry system in cooperation with Village Forest Management (LPHD) are expected to bring prosperity to the community without destroying the forest.